The Fragile Sink: Reconceptualizing Soil Carbon Stabilization and Its Vulnerability Under Global Change - Muhammad Mubashar Iqbal; Muhammad Ansar Farooq; Rattan Lal; Mohamed Abdalla; Pete Smith (Global Change Biology, 2026)
Soil carbon sequestration (SC seq ) is fundamental to global climate mitigation initiatives; however, growing evidence indicates an expanding disparity between carbon (C) accumulation and its long‐term persistence. This article aims to integrate recent advances in microbial ecology, mineral biogeochemistry, and nutrient stoichiometry to examine why increases in soil C (SC) stocks do not necessarily translate into long‐term persistence. The article introduces the fragile sink framework, wherein sink durability reflects the balance between internal C throughput and the strength of stabilizing barriers. Global change drivers, including warming, elevated CO 2 (eCO 2 ), nutrient enrichment, and anthropogenic disturbance, can accelerate internal C turnover, resulting in soils that are structurally younger, more reactive, and increasingly vulnerable to rapid C loss despite stable or rising stocks. The article shows that destabilization begins at predictable vulnerability frontiers where stoichiometric gating and mineral protection are overridden, while recovery is constrained by kinetic and architectural hysteresis. Thus, it recommends a shift away from stock‐ and input‐centric C farming toward process‐centric C defense, emphasizing the protection of slow‐cycling, kinetically protected pools under increasing turnover.